Furan Production from Glycoaldehyde over HZSM-5 - Kim, S; Evans, T; Mukarakate, C; Bu, L; Beckham, G; Nimlos, M; Paton, R; Robichaud, D (American Chemical Society, 2016)
Catalytic fast pyrolysis of biomass over zeolite catalysts results primarily in aromatic (e.g., benzene, toluene, xylene) and olefin products. However, furans are a higher value intermediate for their ability to be readily transformed into gasoline, diesel, and chemicals. Here we investigate possible mechanisms for the coupling of glycoaldehyde, a common product of cellulose pyrolysis, over HZSM-5 for the formation of furans. Experimental measurements of neat glycoaldehyde over a fixed bed of HZSM-5 confirm furans (e.g., furanone) are products of this reaction at temperatures below 300 °C with several aldol condensation products as coproducts (e.g., benzoquinone). However, under typical catalytic fast pyrolysis conditions (>400 °C), further reactions occur that lead to the usual aromatic product slate. ONIOM calculations were utilized to identify the pathway for glycoaldehyde coupling toward furanone and hydroxyfuranone products with dehydration reactions serving as the rate-determining steps with typical intrinsic reaction barriers of 40 kcal mol-1. The reaction mechanisms for glycoaldehyde will likely be similar to that of other small oxygenates such as acetaldehyde, lactaldehyde, and hydroxyacetone. This study provides a generalizable mechanism of oxygenate coupling and furan formation over zeolite catalysts.